Using a modified version of photovoice in a European cross‐national study on homelessness. Issue 1 (9th February 2022) - Gaboardi, Marta; Santinello, Massimo; Lenzi, Michela; Disperati, Francesca; Ornelas, José; Shinn, Marybeth
Abstract: This study proposes an innovative use of a modified version of photovoice for cross‐national qualitative research that allows participants to express their ideas, experiences, and emotions about a topic through photographic language. We examine factors affecting social service providers' work on people experiencing homelessness in Europe. We highlight five advantages of using photovoice in cross‐national research: visual language, methodological flexibility, participatory data analysis, the bottom‐up process, and the promotion of social change. Moreover, we identify key stages of the process: writing a detailed protocol for the implementation and fidelity of the projects, using two levels of data analysis, and disseminating the results. This study provides lessons learned for others who may want to use photovoice in cross‐national research. Highlights: Qualitative methods provide a detailed understanding of people's experiences across countries. This article offers an example of using photovoice to study homeless services in Europe. This study showed the benefit of using photovoice in comparative qualitative research across nations. This study provides recommendations for those who may want to use photovoice in cross‐national research.